Pet Sematary Special Collector's edition - Midkiff, Dale; Gwynne, Fred; Crosby, Denise; Greenquist, Brad; Zinnemann, Tim; Galin, Mitchell; Goldenthal, Elliot; Stein, Peter (Hollywood, California Paramount Pictures Corp., 2000)
The Creeds family just moved in next door to a place that children built with broken dreams, the Pet Semetary. It's a tiny patch of land that hides a mysterious Indian burial ground with the powers of resurrection
Video recordings for the hearing impaired
Closed captioned for the hearing impaired Dialogue in English with optional soundtrack in French; closed-captioned
112795
Keywords: Pet cemeteries; Resurrection